Improvement of the integral indicator for assessing the characteristics of a hybrid power plant as part of a passenger aircraft - Oleksii Pushylin (Авіаційно-космічна техніка та технологія)
The subject of the study in this article is the justification of the efficiency of various architectures of hybrid-electric propulsion system of the turbojet engines. These systems combine thermal energy generated in the combustion chamber of the turbojet engine with electrical energy supplied by onboard batteries or hydrogen fuel cells (FCs). The purpose of the study is to improve the integral indicator of hybridization of the power plant (PP) to assess the contribution of each energy source to the production of mechanical power on the propeller shaft of a hybrid turboelectric power plant (HTEPP). This improvement will broaden the ability to determine the degree of electrification of the PP components and the overall fuel consumption level. The main tasks include: establishing a comprehensive set of key indicators and criteria for evaluating the efficiency of different hybrid-electric propulsion architectures; improving the integral hybridization indicator by quantifying the amount and share of energy generated and consumed from available energy onboard sources. The methods employed in the study are system analysis, mathematical and simulation modeling, as well as retrospective and analytical methods. The main results are as follows: the study analyzed the application of key indicators and criteria in evaluating HTEPP performance. For further research, a sufficient set of main indicators and criteria was established for assessing the efficiency of various hybrid-electric propulsion architectures incorporating electric motors and FC, applicable to aircraft of different sizes. An improved integral indicator was proposed to assess HTEPP characteristics, specifically in the context of light passenger aircraft. The evaluation of HTEPP efficiency requires data on the quantity and share of energy generated and consumed from available onboard sources. The improved integral PP hybridization indicator has a clear physical interpretation, enabling assessment of the contribution of each energy type to the generation of mechanical power on the propeller shaft. Conclusions. The scientific novelty of the study lies in the enhancement of the conceptual framework for the PP hybridization indicator, which includes an integral assessment of hybridization level, considering the energy contribution of each source at different stages of the aircraft flight. Furthermore, the study contributes to the systematization of parameters, characteristics, and factors influencing the management of electrical and thermal energy supply throughout the entire flight cycle.